Reduction in Dietary Nutrient Density Aids in Utilization of High Protein Cottonseed Meal in Broiler Diets - Watkins, S.E.; Saleh, E.A.; Waldroup, P.W. (International Journal of Poultry Science, 2002)
This trial was conducted to determine if the reduction in weight gains and feed intake observed for broilers fed 30% cottonseed meal diets was associated with the high fat level of the diets necessary to maintain the diets isocaloric compared to corn-soybean meal control diets. Three series of energy levels were formulated to contain 2950/3000, 3000/3050, 3050/3100 ME Kcal/kg with values representing the starter/grower (S/G) dietary energy values, respectively. Within each energy series, diets were formulated to contain either soybean meal as the primary protein source (0% CSM) or 30 % cottonseed meal (30 % CSM). Male broilers were fed starter diets 0 to 21 days followed by grower diets to 42 days. At the end of the trial, six birds per pen were processed to determine carcass and parts yield. Results showed that 21 and 42 days body weights, feed consumption and mortality of the birds receiving the 30 % CSM diets were comparable to the performance of birds receiving the 0% CSM diet for the similar energy series. There was an interaction effect for 21 days feed conversion with the feed conversion of the 0% CSM 3000/3050 series significantly lower than all of the other conversion rates. Feed conversion rates at 21 and 42 days were significantly depressed for the birds receiving the 30 % CSM diets. Although the dressing percentage was lower for the 30 % CSM birds, abdominal fat was also lower and breast meat yield equaled the 0 % CSM birds. Increasing the dietary energy level increased abdominal fat. The results indicated that the high dietary fat levels used in previous experiments could to be interfering with optimum usage of a 30 % CSM diet for growth but not for feed conversion.